The Effect Of Aloe Vera Decoction On Blood Cholesterol Levels Of Obese Respondents Level I - Kustiasih Lestari (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2020)
Changes in social trend make many women pursue the career, thus storingbreastmilk cannot be avoided if Hypercholesterolemia is a condition in whichincreased cholesterol levels that exceed normal limits, which have a risk ofdeath of coronary heart disease. Aloe vera is a medicinal plant in Indonesiathat is often used by the community as tradisional medicine. Compoundscontained in Aloe vera namely phytochemicals that contain phenolicscompounds. This study aims to determine the effect of aloe vera boiled waterwith pre and postest research methods. T-tes statiscal results obtained anaverage value of cholesterol level before treatment of 206,34 mg/dL and anaverage after treatment 182,43 mg/dL, meaning that there are differencesin the results of cholesterol levels before and after consuming Aloe veraboiled water. Then it can be concluded that there is a siginicant effect on theprovision of Aloe vera boiled water on the reduction of cholesterol levels inobese respondents level with the p value <0,05.